Aktivitas Antioksidan Sari Buah Delima (Punica granatum L.) pada Beberapa Durasi Penyimpanan dengan Menggunakan Metode DPPH (1,1-diphenil-2-picylhydrazyl) - Devia Rosa Suciati Saragih; Henny Erina Saurmauli Ompusunggu; Jenny Ria Sihombing (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Free radicals can be very dangerous and cause various diseases. Antioxidants are needed to counteract the negative effects of free radicals on the body. Antioxidants can be sourced from fresh fruit, one of which is pomegranate. Nowadays, the busyness of daily life makes people prefer to consume fresh fruit juice packaged in bottles, because it is more practical and easy. However, it’s not known whether or not there is a change in antioxidant activity during several days of storage in the chiller, which could affect the effectiveness of pomegranate in warding off radicals. Based on this, researchers were interested in determining the antioxidant activity of pomegranate (punica granatum L.) juice during chilled and fresh storage using the DPPH (1,1-diphenyl-2-picylhydrazyl) method. This study was a descriptive laboratory experimental study. The research sample comprised pomegranate juice with multiple storage durations, each of which was tested in two replicates. The results showed that at several different storage durations there were different antioxidant activities and IC₅₀  values. The fresher the pomegranate, the greater its ability to inhibit free radical activity. Based on the results of this study, the public is advised to consume pomegranate juice in fresh condition to obtain optimal antioxidant benefits.